Pengaruh Kualitas Pelayanan Terhadap Kepuasan Peserta Event Audisi Pucuk Cool Jam 2024 Pada PT April Untuk Indonesia Di Kota Medan - Azzahra, Adira Jasmine; Siregar, Efni (Civiliza Publishing, 2025)
The Pucuk Cool Jam 2024 audition event was conducted by PT April Untuk Indonesia at the Ringroad Citywalk Medan. Seventy-five participants, consisting of high school and vocational high school students in Medan, participated in the event. This research is categorized as a quantitative study, with the instruments being questionnaires and literature review. The population of the Pucuk Cool Jam 2024 audition event was 75 people. The validity test used SPSS 27, the reliability test used the Crohn's Alpha formula, and multiple linear regression analysis was used to test the research hypotheses. The results of this study indicate that, partially (t-test), the variables of tangibles, reliability, responsiveness, and assurance have positive but not significantly influence participant satisfaction, while the variable of empathy has positive and significantly influenced participant satisfaction at the Pucuk Cool Jam 2024 audition event in Medan. Simultaneously (F-test), the variables of tangible evidence (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) significantly influenced participant satisfaction at the Pucuk Cool Jam 2024 audition event in Medan City, with an adjusted R-square value of 54.7%. The remaining 45.3% can be explained by variables not examined in this study.